2016
DOI: 10.3892/ol.2016.5312
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of MALAT1 and miR-619-5p as a prognostic indicator in advanced colorectal carcinoma

Abstract: Abstract. The present study aimed to detect the expression of metastasis associated lung adenocarcinoma transcript 1 (MALAT1) and microRNA (miR)-619-5p in colorectal carcinoma (CRC), and to evaluate the significance of MALAT1 and miR-619-5p expression in the clinical diagnosis and prognosis of CRC. Quantitative polymerase chain reaction was used to detect MALAT1 and miR-619-5p expression in 120 colorectal carcinoma and 120 adjacent normal tissue samples. The expression levels of MALAT1 and miR-619-5p were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The expression of miR-1273f was signi cantly elevated within exosomes released by hypoxic hepatocellular carcinoma cells than that by normoxic cells, and it could activate the Wnt/β-catenin signaling pathway 29 . Meanwhile, the exosome and plasma levels of miR-619-5p were signi cantly higher in non-small cell lung cancer 30 and prostate cancer cases 31 than in the HCs, whereas the expression level of miR-619-5p was signi cantly lower in colorectal cancer tissues than in normal tissues 32 . Furthermore, miR-150-3p reportedly has diverse expression patterns, in which miR-150 was up-regulated in gastric cancer tissues 33 but down-regulated in lung adenocarcinoma tissues compared with that in normal tissues 34 .…”
Section: Discussionmentioning
confidence: 92%
“…The expression of miR-1273f was signi cantly elevated within exosomes released by hypoxic hepatocellular carcinoma cells than that by normoxic cells, and it could activate the Wnt/β-catenin signaling pathway 29 . Meanwhile, the exosome and plasma levels of miR-619-5p were signi cantly higher in non-small cell lung cancer 30 and prostate cancer cases 31 than in the HCs, whereas the expression level of miR-619-5p was signi cantly lower in colorectal cancer tissues than in normal tissues 32 . Furthermore, miR-150-3p reportedly has diverse expression patterns, in which miR-150 was up-regulated in gastric cancer tissues 33 but down-regulated in lung adenocarcinoma tissues compared with that in normal tissues 34 .…”
Section: Discussionmentioning
confidence: 92%
“…It is identified that miR-619-5p exerts an oncogenic role in OSCC cell lines [25]. A relevant study reported that miR-619-5p suppresses proliferative and invasive capacities of colorectal carcinoma cells [42]. A latest report demonstrated that miR-619-5p enhances sensitivity of pancreatic cancer cells to gemcitabine via activating the Wnt/β-catenin signaling pathway [26].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-1273f was signi cantly elevated within exosomes released by hypoxic hepatocellular carcinoma cells than that by normoxic cells, and it could activate the Wnt/β-catenin signaling pathway (29). Meanwhile, the exosome and plasma levels of miR-619-5p were signi cantly higher in non-small cell lung cancer (30) and prostate cancer cases(31) than in the HCs, whereas the expression level of miR-619-5p was signi cantly lower in colorectal cancer tissues than in normal tissues (32). Furthermore, miR-150-3p reportedly has diverse expression patterns, in which miR-150 was up-regulated in gastric cancer tissues(33) but down-regulated in lung adenocarcinoma tissues compared with that in normal tissues (34).…”
Section: Discussionmentioning
confidence: 99%